2015
DOI: 10.1111/hsc.12259
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the use of social support services among elderly people living in a city environment in Poland

Abstract: Ageing populations entail important social issues. The population of Lodz is characterised by the highest ageing ratio in Poland (17.2% people aged 65 or above). The aim of our study was to present factors determining the use of social support services in the subpopulation of elderly people in a city environment. The study, conducted between 2011 and 2012 with the use of a survey questionnaire, included 466 respondents aged 65 or older, who were looked after by the Municipal Social Welfare Centre, Lodz-Polesie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…4 Studies conducted in Brazil, Poland, Spain, and China revealed that the use of health care services by the elderly was mainly associated with education level, self-reported health status, limited activity, and the number of chronic diseases. [5][6][7][8] Additionally, empirical evidence showed that as much as three quarters of the total health care expenses were related to the treatment of chronic diseases in the elderly. 9 High medical expenses create the problem of inadequate financial affordability of access to appropriate care for the elderly and the risk of catastrophic health expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…4 Studies conducted in Brazil, Poland, Spain, and China revealed that the use of health care services by the elderly was mainly associated with education level, self-reported health status, limited activity, and the number of chronic diseases. [5][6][7][8] Additionally, empirical evidence showed that as much as three quarters of the total health care expenses were related to the treatment of chronic diseases in the elderly. 9 High medical expenses create the problem of inadequate financial affordability of access to appropriate care for the elderly and the risk of catastrophic health expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…The deterioration of the senior's functional status decreases their perceived quality of life, which is aggravated by reduced compensatory abilities and more frequent occurrence of concomitant diseases [20]. Analyses performed by Kolotkin [21] imply a lower quality of life indicator in the physical domain among elderly people and show that quality of life depends on disease type and duration.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of infrastructure and improvement in access to various services in rural area (e.g. health-care services) has also helped in eliminating the differences between urban and rural inhabitants [48]. In many countries, particularly those that are developing, very high significant differences in disability level were noticed between the inhabitants of urban and rural areas.…”
Section: Discussionmentioning
confidence: 99%